Implementation of Building Information Modelling (BIM 3D) on the Steel Building project: Case study of the 3-storey building GKJ MARGOYUDAN - Sungkono, Kukuh Kurniawan Dwi; Sukwadi, Ronald (Science and Technology Research Centre, Universitas PGRI Semarang, 2022)
Building Information Modelling (BIM) is a technological revolution developed in the construction industry. The implementation of BIM using Tekla Structure software helps overcome problems in the 3-story steel building construction project. Integration of the structural analysis software and Tekla Structure BIM, making the design phase efficient. Detailed drawings generated at the design stage using analysis software and BIM, lead to efficient construction exploration and evaluation. Tekla Structure produces detailed drawings and a list of required materials, which can help contractors in project management. Simultaneous management of activities between site and workshop, providing the advantage of project completion on schedule. Procurement of materials and errors during construction can be minimized, thereby optimizing project costs.